2013
DOI: 10.1080/02701960.2012.679372
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Older Adults Into the Classroom: The Sharing Community Model

Abstract: This article describes an innovative model for teaching gerontological social work that has been introduced into the social work methods curriculum in the Department of Social Work at a college in northern Israel. The basic concept of the model is to create an alternative learning environment by including older persons as full participants in the classroom. As experts on old age, they provide social work students with a hands-on learning experience intended to facilitate their understanding of aging. The chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The findings suggest that stereotypes of aging may be lessened upon successful completion of the exercise and participation in the misconceptions discussion [51]. Hantman et al [52] conducted a study on the effectiveness of an intergenerational classroom during a yearlong social work course. The objective was to help students gain understanding and awareness of the aging process, interpersonal skills, age sensitivity, and enhance feelings of mutuality and equality, and they found that students developed in these areas, broke down barriers, and had a positive perspective change towards older adults [52].…”
Section: Programs and Interventions For Reducing Ageismmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings suggest that stereotypes of aging may be lessened upon successful completion of the exercise and participation in the misconceptions discussion [51]. Hantman et al [52] conducted a study on the effectiveness of an intergenerational classroom during a yearlong social work course. The objective was to help students gain understanding and awareness of the aging process, interpersonal skills, age sensitivity, and enhance feelings of mutuality and equality, and they found that students developed in these areas, broke down barriers, and had a positive perspective change towards older adults [52].…”
Section: Programs and Interventions For Reducing Ageismmentioning
confidence: 99%
“…Hantman et al [52] conducted a study on the effectiveness of an intergenerational classroom during a yearlong social work course. The objective was to help students gain understanding and awareness of the aging process, interpersonal skills, age sensitivity, and enhance feelings of mutuality and equality, and they found that students developed in these areas, broke down barriers, and had a positive perspective change towards older adults [52]. Another program, "Time After Time," included both creative and artistic based activities in which older adults interacted with younger people daily for several weeks.…”
Section: Programs and Interventions For Reducing Ageismmentioning
confidence: 99%
“…Social work in Israel in the field of gerontology includes five main areas: (a) the elderly, (b) their families, (c) the elderly community, (d) social and health services, and (e) the larger social environment (Hantman, Oz, Gutman & Criden, 2013). The involvement of social workers in these areas is derived from the needs of the elderly population, according to the goals and values of the social work profession.…”
Section: The Role Of the Social Worker In Integrating Fhcwsmentioning
confidence: 99%
“…Those who are more knowledgeable about aging tend to have less ageist attitudes and are less anxious about aging themselves (Allan & Johnson, 2008). Educators have identified a variety of classroom activities (Knapp & Stubblefield, 2000;Ligon, Ehlman, Moriello, & Welleford, 2009) and approaches (Hantman, Oz, Gutman, & Criden, 2013) that may promote development of more positive attitudes.…”
mentioning
confidence: 97%